1994
DOI: 10.1007/bf01400871
|View full text |Cite
|
Sign up to set email alerts
|

Meningiomas: Correlation between MRI characteristics and operative findings including consistency

Abstract: The findings on magnetic resonance imaging (MRI) in 73 surgically verified intracranial meningiomas were correlated with their histology and consistency during resection. T 1-weighted imaging was least useful since most of the tumours were iso-intense, similar to cortical grey matter regardless of histology or tumour consistency. The signal intensity on T2-weighted images was found to best correlate with both the histology and consistency of the meningioma. Generally, the low intensity portion of the tumour on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
2
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 12 publications
3
43
2
1
Order By: Relevance
“…Over the past 2 decades, numerous studies have attempted to predict the consistency of cranial meningiomas by using a variety of advanced MRI techniques, ranging from T2-weighted to diffusion-tensor imaging to MR elastography sequences, mainly with limited success. 1,2,6,7,15 A prior study by Chen et al, from our institution, did show a correlation between soft tumor consistency and hyperintensity on T2-weighted MRI, 2 as have some additional studies. 6,9,12,15,19 Two prior studies have demonstrated an association between hard tumors and the fibroblastic meningioma subtype.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Over the past 2 decades, numerous studies have attempted to predict the consistency of cranial meningiomas by using a variety of advanced MRI techniques, ranging from T2-weighted to diffusion-tensor imaging to MR elastography sequences, mainly with limited success. 1,2,6,7,15 A prior study by Chen et al, from our institution, did show a correlation between soft tumor consistency and hyperintensity on T2-weighted MRI, 2 as have some additional studies. 6,9,12,15,19 Two prior studies have demonstrated an association between hard tumors and the fibroblastic meningioma subtype.…”
Section: Discussionmentioning
confidence: 62%
“…1,2,6,7,15 A prior study by Chen et al, from our institution, did show a correlation between soft tumor consistency and hyperintensity on T2-weighted MRI, 2 as have some additional studies. 6,9,12,15,19 Two prior studies have demonstrated an association between hard tumors and the fibroblastic meningioma subtype. 1,7 Other studies, however, have found no relationship between imaging findings and consistency 17 or between histology and consistency.…”
Section: Discussionmentioning
confidence: 62%
“…26 Although some authors have reported limited success in the ability to predict tumor consistency based on advanced preoperative imaging modalities, such as T2-weighted MR imaging, diffusion weighted MR imaging, and diffusion tensor MR imaging, the reliability of these techniques is not such that they are widely used to provide this critical information. 4,11,14,30,32,59,62 Promising modalities for predicting tumor consistency include MR imaging or ultrasound elastography. 44,60,61 In the future, a priori knowledge of tumor consistency may lend major support to the selection of a skull base approach from above versus below and warrants further research.…”
Section: Lateral Extension Beyond the Cavernous Sinusmentioning
confidence: 99%
“…Several earlier studies assessed the ability of conventional MR imaging for determining the consistency of pituitary adenomas (1)(2)(3)(4)(5)(6) or meningiomas (7)(8)(9)(10)(11). Only a few studies evaluated the consistency of pituitary macroadenomas using apparent diffusion coefficient (ADC) with diffusion weighted imaging (DWI) (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%